Environmental psychology : an analysis on lighting efficiency of the architecture studio in UiTM Perak / Fazidah Hanim Husain, Zafuan Husri and Farhah Amani - Husain, Fazidah Hanim; Husri, Zafuan; Amani, Farhah (2015)
Lighting is one of the key elements in any space and building infrastructure. Good design for a space in the building requires sufficient light that contribute to the efficiency of an activity. The correct method allows natural light to transmit, reduce heat and glare in providing a conducive learning environment. Light plays a significant influence to the quality of space and contribute focus of the students in an architecture studio. Previous research has shown that emotions, behavior and mood of the students were also controlled by the effect of light. The operations of artificial lighting that have been used most of the time in an architecture studio during day and night may create lavishness and inadequacy at the same time. Therefore, this paper focuses to identify the quality of lighting of the architecture studio in UiTM Seri Iskandar, in order to instill a creative learning environment. The methodology of this analysis is providing lighting measurement by using the equipment named LM-8100, using a questionnaire in gauging the lighting comfort level from students’ perspective. Findings from the analysis will determine the level of lighting settings in accordance to the Malaysian Code of Practice on Indoor Air Quality standards. The result will identify the students’ creative performance on the learning activities in their studio.